Online Marketing Mix’s influencing the Decision to Buy Skincare Through Social Media - เจริญชัย กิตติชัย; ANH TUAN , HUYNH PHAN; Chotcheuy, Nisarat (Journal for Developing the Social and Community, 2023)
The objectives of the research were 1. To study the level of online marketing mix’s influencing the decision to buy skincare through social media. 2. To study the process of decision to purchase of buy skincare through social media. 3) To compare the online marketing mix influencing the buying decision process of Skincare products Through Social Media 4) To compare the process of decision to purchase of buy skincare through social media. and 5. To study the influence of Online Marketing Mix factors affecting on process of decision to buy skincare through social media. The sample population consisted of 385 consumers who bought Skincare Through Social Media. The research instrument was a questionnaire. The statistics used in data analysis were frequency, percentage, mean, and standard deviation. The techniques of t test, F-test (One-way ANOVA), and multiple regression analysis were also employed. The results were as follows: 1. The level of the importance of online marketing mix was at the high level. 2. The level of the process of decision to purchase of Skincare Through Social Media was at the highest level. 3. The comparison of the online marketing mix influencing the buying decision process of Skincare products Through Social Media which classified by age was difference with statistically significant at 0.05 level and classified by gender was no difference 4. The comparison of the buying decision process of Skincare Through Social Media which classified by age was difference with statistically significant at 0.05 level and classified by gender was no difference. And 5. Marketing mix affecting the buying decision process of Skincare Through Social Media in descending order was as follows: AdjR2=.643, personalization (β =.560); place (β =.370); price (β = .121); and product (β =.284) at the statistically significant level of .05.